Complete chloroplast genome of novel Adrinandra megaphylla Hu species: molecular structure, comparative and phylogenetic analysis - Huu Quan Nguyen (Nature Portfolio, 2021)
Abstract Adrinandra megaphylla Hu is a medicinal plant belonging to the Adrinandra genus, which is well-known for its potential health benefits due to its bioactive compounds. This study aimed to assemble and annotate the chloroplast genome of A. megaphylla as well as compare it with previously published cp genomes within the Adrinandra genus. The chloroplast genome was reconstructed using de novo and reference-based assembly of paired-end reads generated by long-read sequencing of total genomic DNA. The size of the chloroplast genome was 156,298 bp, comprised a large single-copy (LSC) region of 85,688 bp, a small single-copy (SSC) region of 18,424 bp, and a pair of inverted repeats (IRa and IRb) of 26,093 bp each; and a total of 51 SSRs and 48 repeat structures were detected. The chloroplast genome includes a total of 131 functional genes, containing 86 protein-coding genes, 37 transfer RNA genes, and 8 ribosomal RNA genes. The A. megaphylla chloroplast genome indicated that gene content and structure are highly conserved. The phylogenetic reconstruction using complete cp sequences, matK and trnL genes from Pentaphylacaceae species exhibited a genetic relationship. Among them, matK sequence is a better candidate for phylogenetic resolution. This study is the first report for the chloroplast genome of the A. megaphylla.